Features of goal kicks by football players in games of high-level teams - Andrii Pertsukhov; Borys Beziazychnyi; Viktoria Khudiakova (Kharkiv State Academy of Physical Culture, 2020)
Purpose: to establish the peculiarities of goal kicks by highly qualified football players in the conditions of competitive activity. Material & Methods: the registration of technical and tactical actions was carried out using the games of teams participating in the group stage of the UEFA Champions League 2019/2020 season as an example. The games of Group C teams of FC Manchester City (Manchester City, England), FC Atalanta (Bergamo, Italy), FC Shakhtar (Donetsk, Ukraine), FC Dynamo (Zagreb, Croatia) were analyzed. In total, 290 shots were recorded and analyzed in 12 games of four teams. To solve the tasks in the work, the following research methods were used: analysis of scientific and methodological literature, registration of team technical and tactical actions, methods of mathematical statistics. Results: the paper presents data that characterize the features of kicks by players in the games of high-level teams. In total, 290 kicks were recorded and analyzed in 12 games of four teams participating in the UEFA Champions League 2019/2020 season. Kicks on goal were classified according to the result (goals, on target, past the goal, into the goal frame, blocked shots), at the place of execution (from the goal area, from the penalty area, from outside the penalty area), along the trajectory (upwards kicks, low kicks). Conclusions: the results of the study indicate differences in the quantitative indicators of kicks on goal of teams participating in the UEFA Champions League season 2019/2020 in group "C". It was established that highly qualified football players most often performed kicks on the right foot, which is explained by the lateral advantage. In addition, football players carried out more kicks from the bottom and from the zone between the goal area line and the penalty area line, which should be reflected in the construction of exercises aimed at improving the technique and tactics of kicks.